QUALITY INDICES OF SOYBEAN SEEDS DEPENDING ON THE INFLUENCE OF MINERAL AND BACTERIAL FERTILIZERS - Шевніков, М. Я.; Міленко, О. Г.; Лотиш, І. І. (Scientific Progress & Innovations, 2014)
The influence of mineral nitrogen and “Rizotorfin” is reflected on an accumulation of an albumen and fat in the seed of soy. The inoculation of “Rizotorfin” and bringing of mineral fertilizers, their especially compatible application, entailed the considerable increase of maintenance in the seed of albumen and diminishing of content of fat. Bacterial fertilizers positively influenced on the increase of content of fat in the seed of soy - 18,1 %, but more rational was a complex action of mineral and bacterial fertilizers that promoted content of fat in the dry substance of seed to 21,4-22,4 %.